METHODS FOR THE TRAINING OF FUTURE IT SPECIALISTS IN STRATEGIC AND TACTICAL ACTIVITIES IN BUSINESS ORGANIZATIONS - Lavrentieva Olena; Krupskyi Oleksandr (Vìsnik Unìversitetu ìmenì Alʹfreda Nobelâ: Serìâ Pedagogìka ì Psihologiâ, 2023)
The article emphasizes the relevance of revising the content of professional activities and the range of powers of specialists of IT departments in business organizations and, accordingly, the conceptual foundations of their professional training. The need for forming future IT specialists with unique skills and abilities to carry out strategic and tactical activities and develop the relevant competencies, which allows them to be active participants in the construction and implementation of the organization’s business strategies, has been clarified. The purpose of the article is to review and analyse the features of strategic and tactical activities in the functioning of IT specialists in a business organization, as well as the study of methodological foundations of the formation of tactical and strategic competence in future IT specialists, which will allow them to implement various measures of strategic planning and project work successfully. During the study of the problem of training future IT specialists for strategic and tactical activities in business organizations, methods of retrospective analysis, generalization and interpolation of theoretical aspects of the problem were applied; methods of conceptualizing advanced pedagogical experience in the formation of professional important competencies of future IT specialists were used. It has been found that tactical and strategic competence determines the ability of an IT specialist to project short-term and long-term goals, develop methods and tactics for their achievement, and in this way effectively organize professional activity and achieve success in it. It has been substantiated that the development of tactical and strategic competence can be realized in terms of a specially organized training process for future IT specialists contributing to their mastering the experience of developing and approbation IT strategies and tactics. Methodological approaches (competent-oriented, creative-developmental, multidisciplinary, practice-oriented, problem-based ones) have been revealed, for them the methods of training future IT specialists for strategic and tactical activities in business organization should be based. It has been noted that the methods of formation of future IT specialists’ readiness for strategic and tactical activities involve a number of stages, namely: 1) actualization of professional needs, interests, motives, and formation of students’ business values; 2) determination of the goal and selection the tools of influence aimed at the shaping of students’ scientific and theoretical knowledge and personal experience in the implementation of professional skills; 3) arming students with an arsenal of strategies that allow for a holistic analysis of the situation, actions, and motives and, as a result, permits to reduce the operational costs of the organization and the turned IT service into a driver of business; 4) modelling of possible strategy implementation tactics in various production situations; 5) analysis of acquired experience, control and correction of formation of future IT specialists’ professionally important competencies. The features of the application of methods of activation and stimulation of motivation and responsibility in educational and professional activities, organizational methods, the method of immersion in the situation, the method of pattern and case study in the process of formation of tactical and strategic competence in future IT specialists have been defined and described. A conclusion was made regarding the requirement for step-by-step application of methods and technologies in order to prepare future IT specialists for strategic and tactical activities during their professional training process.